Health visiting in the UK in light of the COVID-19 pandemic experience (RReHOPE): a realist review protocol. Issue 3 (8th March 2023) - King, Emma; Gadsby, Erica; Bell, Madeline; Duddy, Claire; Kendall, Sally; Wong, Geoff
Abstract : Introduction: Health visiting services, providing support to under 5s and their families, are organised and delivered in very different ways in different parts of the UK. While there has been attention to the key components of health visiting practice and what works well and how, there is little research on how health visiting services are organised and delivered and how that affects their ability to meet their objectives. The COVID-19 pandemic rapidly disrupted service delivery from March 2020. This realist review aims to synthesise the evidence on changes during the pandemic to identify the potential for improving health visiting services and their delivery. Methods and analysis: This review will follow the RAMESES (Realist And Meta-narrative Evidence Syntheses: Evolving Standards) quality standards and Pawson's five iterative stages to locate existing theories, search for evidence, select literature, extract data, synthesise evidence and draw conclusions. It will be guided by stakeholder engagement with practitioners, commissioners, policymakers, policy advocates and people with lived experience. This approach will consider the emerging strategies and evolving contexts in which the services are delivered, and the varied outcomes for different groups. A realist logic of analysis will be used to make sense of what was happening to health visiting services during and following the pandemic response through the identification and testing of programme theories. Our refined programme theory will then be used to develop recommendations for improving the organisation, delivery and ongoing postpandemic recovery of health visiting services. Ethics and dissemination: General University Ethics Panel approval has been obtained from University of Stirling (reference 7662). Dissemination will build on links to policymakers, commissioners, providers, policy advocates and the public. A range of audiences will be targeted using outputs tailored to each. A final stakeholder event focused on knowledge mobilisation will aid development of recommendations. PROSPERO registration number: CRD42022343117.